THE IMPACT OF DIVIDEND ANNOUNCEMENT ON STOCK RETURNS AMONG THE TEN TOP COMPANIES IN PAKISTAN - Zubair Tanveer; Muhammad Jamil (Malaysian Management Journal, 2020)
The study tested the response of stock prices around the dividend declaration dates in Pakistan stock exchange. It estimated the data of 1110 dividends announced by 91 firms of the highest ten active sectors of Pakistan Stock Exchange. To empirically investigate the relationship between stock returns and dividend announcement, the panel regression was employed by creating dummy variables for 61 days around the dividend declaration dates. Cumulative average abnormal returns and average abnormal returns were also stimated around the events with the help of event study methodology. Outcomes of the empirical analysis revealed strong evidence of market abuse in the term of insider trading and supported the argument of the information content hypothesis and semistrong form of efficient market. Moreover, the study also found a robust impact of the probable ex-dividend date. The study recommended that it is a responsibility of stock exchange regulatory authorities, whistleblowers, registered companies, and the investors collectively to detect and punish this white-collar financial crime.